Comparative Growth Performances of Tea Saplings Raised in the Poly and Gunny Bags - Rana, MM; Hossain, SMA; Hossain, MI; Huq, MS; Rahman, MM (Bangladesh Agronomy Journal, 2016)
Abstract not available Bangladesh Agron. J. 2016, 19(1): 109-113